1996
DOI: 10.1177/107110079601701005
|View full text |Cite
|
Sign up to set email alerts
|

Bridle Transfer for Paresis of the Anterior and Lateral Compartment Musculature

Abstract: In the Riordan (bridle) transfer, the posterior tibialis muscle as motor is routed through the interosseous membrane and anastomosed into a "bridle" formed by the distal tibialis anterior and peroneus longus muscles. In theory, the bridle provides inversion/eversion balance even if the transfer effects only tenodesis. However, the procedure has been criticized because its insertion is not into bone. This review analyzes the use of bridle transfer in flaccid paresis involving musculature innervated by the peron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 6 publications
2
43
0
3
Order By: Relevance
“…De Marchi et al [4] concluded that there was no deterioration in function with time in patients who had the distal attachment to the cuneiform, while Prahinski et al [16] commented that function deteriorated in time due to the tendon stretching out. We are not able to comment on this phenomenon, except to report that one patient felt that dorsiflexion was weaker following her pregnancy, and another felt this following a recent fall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De Marchi et al [4] concluded that there was no deterioration in function with time in patients who had the distal attachment to the cuneiform, while Prahinski et al [16] commented that function deteriorated in time due to the tendon stretching out. We are not able to comment on this phenomenon, except to report that one patient felt that dorsiflexion was weaker following her pregnancy, and another felt this following a recent fall.…”
Section: Discussionmentioning
confidence: 99%
“…The medial tail was inserted into the tendon of extensor hallucis longus and the lateral tail into the tendons of extensor digitorum longus and peroneus tertius. The Bridle procedure [14], a tritendon double-end-weave anastomosis between tibialis posterior, tibialis anterior and peroneus longus tendon was used by Prahinski et al [16] to treat 10 soldiers.…”
Section: Introductionmentioning
confidence: 99%
“…Given that many patients have acquired a foot drop by a longitudinal traumatic stretch injury to the peroneal nerve, neurolysis and/or nerve grafting has not resulted in successful restoration of ankle dorsiflexion [17,22]. Posterior tibial tendon transfers and their variants, although a reasonable treatment option for foot drop, provides only weak ankle dorsiflexion [15] and is fraught with long-term complications [5]. Nerve transfers Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior tibial tendon transfers and their variants (Bridle procedure, Riordan transfer) are a commonly used treatment for foot drop [6]. Although this tendon transfer has had reasonable success in allowing patients to return to ambulation without assistive devices [6], the procedure provides weak dorsiflexion and may not completely restore normal gait [15]. This procedure is fraught with long-term complications, including hindfoot valgus deformity, arthritis, and flat foot deformity [5].…”
Section: Introductionmentioning
confidence: 99%
“…The most common such procedure has been the transfer of all or a portion of the tibialis posterior tendon, redirected to the dorsum of the foot. This provides weak ankle dorsiflexion and may not completely correct the gait problem (Prahinski et al, 1996); furthermore, long-term complications, including hind-foot valgus deformity, arthritis, and flatfoot deformity, have been reported (Johnson and Strom, 1989).…”
Section: Introductionmentioning
confidence: 99%